2022
DOI: 10.2174/1573407217666211119092552
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile, Acute Toxicity, and Hepatoprotective and Antiproliferative Activities of Algerian Ruta tuberculata Forssk

Abstract: Objective: Ruta tuberculata forssk. (Rutaceae) is an aromatic plants widely used in Algerian traditionally medicine due to its pharmaceutical virtues against various disorders. This study aims to determine the phenolic profile of aqueous (RAE) and methanol (RME) extracts of R. tuberculata aerial parts and to investigate their acute oral toxicity, as well as their possible antiproliferative and hepatoprotective effects. Methods: Polyphenols were identified by quantitative LC-MS/MS analysis. Oral acute toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Moreover, quercetin and catechin were only determined by cLC-DAD in both concerning extracts, in which the higher amounts were quantified in RME. Indeed, the richness of this extract in flavonoids content has been confirmed by both analysis methods [ 3 ].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, quercetin and catechin were only determined by cLC-DAD in both concerning extracts, in which the higher amounts were quantified in RME. Indeed, the richness of this extract in flavonoids content has been confirmed by both analysis methods [ 3 ].…”
Section: Discussionmentioning
confidence: 79%
“…Several phytochemical studies reported on the richness of Ruta species in polyphenols and flavonoids [ 3 , 13 , 17 , 18 ], while a limited number of reports on phenolic screening of Ruta tuberculata (or Hapophyllum tuberculatum ) could be found in scientific literature. In this context, the actual lack of studies that focus on the phenolic characterization in different extracts of R. tuberculata from Algeria increased our interest and curiosity to study it in depth and motivated us to characterize the phenolic compounds of crude polar extracts of their aerial parts, using cLC-DAD quantitative analysis, but also to evaluate their pharmacological effects using both in vitro and in vivo approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations